PEMANFAATAN MEDIA SOSIAL SEBAGAI SARANA INFORMASI DAN PROMOSI DI SDN SUMBER 2 - Andriani, Ria; Slameto, Andika Agus; Mahnunah, Nimah; Sa'di, Ahmad (Jurnal Abdi Insani, 2024)
The use of social media as a means of information and promotion has become an important strategy in the world of education, including in elementary schools. The purpose of this community service is to provide training on the use of Social Media as a Means of Information and Promotion in order to improve the ability of human resources responsible for managing Social Media, in this case we focus on Instagram. The methods used in this activity include training, mentoring, and evaluation of the use of school social media. This training has succeeded in improving the understanding and skills of teachers and school staff in using social media and managing digital assets of SDN Sumber 2. In addition, training participants now understand how to use social media effectively as a tool for information and promotion. They learned about the importance of consistency in posting, how to create interesting content, and strategies to increase audience engagement.